The effect of training intensity on ratings of perceived exertion - Haskvitz, E M; Seip, R L; Weltman, J Y; Rogol, A D; Weltman, A (International journal of sports medicine, 1992)
We examined the effects of intensity of training on ratings of perceived exertion (RPE) at the lactate threshold (LT), fixed blood lactate concentrations (FBLC) of 2.0, 2.5 and 4.0 mM and peak in 25 untrained eumenorrheic women (mean +/- SD: age = 30.9 +/- 4.1 yrs; height = 165.7 +/- 5.9 cm; weight = 65.5 +/- 7.6 kg) who completed one year of run training. Subjects were recruited as sedentary controls or were randomly assigned to one of two training groups: 1) at the lactate threshold (at LT) or 2) above the lactate threshold (greater than LT). The at LT group trained at velocity LT and the greater than LT group trained at the velocity midway between velocity LT and peak velocity. Training subjects were reevaluated every fourth menstrual cycle and training intensity was adjusted. The control group was reassessed at menstrual cycle 12. Before training no among group differences were observed for VO2 or velocity at LT, FBLC and peak. Both training groups increased VO2 at LT, FBLC and peak as a result of training (p less than 0.05), with the greater than LT group exhibiting greater improvement than the at LT group (VO2 at LT, FBLC of 2.0, 2.5 and 4.0 mM and peak increased by 6.4, 5.3, 5.1, 4.0 and 4.7 ml/kg.min-1 for at LT and by 10.4, 9.2, 8.6, 5.1 and 5.9 ml/kg.min-1 for greater than LT; p less than 0.05). Similar findings were observed for the velocity associated with these lactate concentrations. No pre/post differences were observed in VO2 or velocity for the control group.